The Albania National Employment Service Functional Review : An Overview - World Bank Group (World Bank, Washington, DC, 2018)
Albania’s labor markets improved between 2014 and 2016 where more people than before found jobs and unemployment rates fell. However, many challenges remain to channel the jobless into jobs. Efficient and effective public employment services aimed at fostering successful job matching can make a significant difference in reducing unemployment rates. Certain types of job matching might be especially valuable for the poor and vulnerable, who tend to be less connected with economic opportunities. The role of Albania’s National Employment Service (NES) is to assist jobseekers in job search and increase their employability or capacity for entrepreneurship, through skills training and other active labor market programs (ALMPs). The services offered by the NES include registration of jobseekers, job intermediation, counseling services and guidance for jobseekers, preparation of and checking eligibility documents for unemployment benefits, vocational training, and employment promotion. A core part of Albania’s current reform program is to increase the capacity of public institutions to provide effective public services, including modern performance management of the NES. This overview note provides a summary of the main findings of the analysis, with a focus on providing policy-relevant insights. This note provides a brief description of the labor market challenges and constraints facing the NES (Section 2), an overview of the methodology (Section 3), and a summary of key findings (Section 4). Section 5 concludes.